Implikasi Yuridis Kebijakan Formulasi Alat Bukti Elektronik - Eko Surya Prasetyo; Y.A. Triana Ohoiwutun; Halif Halif (Lentera Hukum, 2018)
Formulation policy occupies a strategic role in the efforts to eradicate criminal acts, as law enforcers are bounded by prevailing laws and regulations. The issue of article formulation is only the surface of the problem when using electronic evidence in practice. The Law Number 31, Year 1999, on Corruption Criminal Act acknowledges electronic evidence as an extension of “petunjuk”, while in The Law Number 8 Year 2010, the Money Laundering Criminal Act, electronic evidence is recognized as an independent instrument of evidence. This article examines the underlying reasons for differences in formulation policy, in terms of the legislator's rationales. This article will also expose juridical implications for the recognition of electronic evidence in both acts. The article uses normative yudiris-legal research that analyses law through a building norm system. Based on legislative review, by tracking the legislation rationale, it is found that there is no fundamental reason for the classification, but it is only a legal policy because of legislation Based on the conceptual study, it is understood that electronic evidence, “petunjuk”, is weaker than independent evidence. This article concludes with the suggestion to include electronic evidence in the Criminal Procedure Code (KUHAP), with a ‘stand-alone’ position that is not part of other evidence. Keywords: Formulation Policy, Electronic Evidence